Cascading effects of predators on algal size structure. Issue 2 (3rd February 2022) - Rober, Allison R.; McCann, Kevin S.; Turetsky, Merritt R.; Wyatt, Kevin H.
Abstract : The presence of edible and inedible prey species in a food web can influence the strength that nutrients (bottom‐up) or herbivores (top‐down) have on primary production. In boreal peatlands, wetter more nutrient‐rich conditions associated with ongoing climate change are expanding consumer access to aquatic habitat and promoting sources of primary production (i.e., algae) that are susceptible to trophic regulation. Here, we used an in situ mesocosm experiment to evaluate the consequences of enhanced nutrient availability and food‐web manipulation (herbivore and predator exclusion) on algal assemblage structure in an Alaskan fen. Owing to the potential for herbivores to selectively consume edible algae (small cells) in favor of more resistant forms, we predicted that the proportion of less‐edible algae (large cells) would determine the strength of top‐down or bottom‐up effects. Consistent with these expectations, we observed an increase in algal‐cell size in the presence of herbivores (2‐tiered food web) that was absent in the presence of a trophic cascade (3‐tiered food web), suggesting that predators indirectly prevented morphological changes in the algal assemblage by limiting herbivory. Increases in algal‐cell size with herbivory were driven by a greater proportion of filamentous green algae and nitrogen‐fixing cyanobacteria, whose size and morphological characteristics mechanically minimize consumption. While consumer‐driven shifts in algal assemblage structure were significant, they did not prevent top‐down regulation of biofilm development by herbivores. Our findings show that increasing wet periods in northern peatlands will provide new avenues for trophic regulation of algal production, including directly through consumption and indirectly via a trophic cascade.